"Z matki obcej--" : szkice o powiazaniach Mickiewicza ze swiatem Zydow - Maurer, Jadwiga (Londyn : Polska Fundacja Kulturalna, 1990)
A short study on the relationship of the poet Mickiewicz with the Jewish world of his time.
Includes bibliographical references (p. 137-138) and index.
Keywords: Mickiewicz, Adam, -- 1798-1855 -- Knowledge -- Jews; Mickiewicz, Adam, -- 1798-1855.; Jews in literature